Interview with Artist Rob Shetterly - Staff, Editorial (Maine Policy Review, 2018)
Artist Rob Shetterly has been creating MPR covers for 20 years. In this article he describes his artistic ambition to be a surrealist, that is, to create visual metaphors for the issues he thought most important and how he brings that sensibility to Maine Policy Review covers.
Keywords: Maine Policy Review; cover art